2009
DOI: 10.1177/1363461509105822
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leisure in the Lives of Psychotic Patients: A Qualitative Study

Abstract: Quality of life is defined by indicators that measure the life patterns of a person or community in relation to an ideal model. Leisure is an important component of quality of life and a tool for rehabilitation for patients with chronic psychosis. This qualitative study evaluated the role of leisure in the life of patients living with psychosis. Interviews with patients and relatives indicate that sociability is an important value for both groups. Deeper analysis, however, indicates that sociability is a cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…However, music therapy studies have recently demonstrated positive effects on negative symptoms and social functioning for patients with severe mental illness (Gold et al, 2013 ; Gold, Solli, Krüger, & Lie, 2009 ; Mössler, Chen, Heldal, & Gold, 2011 ). Other research indicates that sociability and satisfying social networks are important factors as they are associated with enhanced hope (Adams & Partee, 1998 ; Byrne et al, 1994 ), well-being (Jetten, Haslam, Haslam, Dingle, & Jones, 2014 ; Kogstad, Mönness, & Sörensen, 2013 ; Ponde, Peireira, Leal, & Oliveira, 2009 ), and quality of life (Hansson, 2006 ). The World Health Organization’s (WHO) review of the evidence for social determinants of health concludes that “Belonging to a social network of communication and mutual obligation makes people feel cared for, loved, esteemed and valued.…”
Section: Introductionmentioning
confidence: 99%
“…However, music therapy studies have recently demonstrated positive effects on negative symptoms and social functioning for patients with severe mental illness (Gold et al, 2013 ; Gold, Solli, Krüger, & Lie, 2009 ; Mössler, Chen, Heldal, & Gold, 2011 ). Other research indicates that sociability and satisfying social networks are important factors as they are associated with enhanced hope (Adams & Partee, 1998 ; Byrne et al, 1994 ), well-being (Jetten, Haslam, Haslam, Dingle, & Jones, 2014 ; Kogstad, Mönness, & Sörensen, 2013 ; Ponde, Peireira, Leal, & Oliveira, 2009 ), and quality of life (Hansson, 2006 ). The World Health Organization’s (WHO) review of the evidence for social determinants of health concludes that “Belonging to a social network of communication and mutual obligation makes people feel cared for, loved, esteemed and valued.…”
Section: Introductionmentioning
confidence: 99%